2020
DOI: 10.1002/jctb.6633
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming multi‐resistant leishmania treatment by nanoencapsulation of potent antimicrobials

Abstract: Leishmaniasis corresponds to a group of neglected tropical diseases caused by flagellated protozoa belonging to the Leishmania genus. This widely spread illness is found in over 90 countries in tropical and sub-tropical regions and also in southern Europe. As parasites exclusively infect highly phagocytic cells (macrophages), this aspect can be exploited for targeted delivery making use of nanoparticles. Drug-loaded nanoparticles have been proposed for improving the bioavailability of classical drugs commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 128 publications
(144 reference statements)
0
7
0
Order By: Relevance
“…Leishmania parasites are transmitted to humans through the bite of female sandflies of the genera Lutzomyia and Phlebotomus. Like many protozoan parasites, Leishmania parasites have a digenetic lifecycle: an extracellular mobile stage (promastigote), exclusive to the invertebrate host, and an intracellular (amastigote) non-mobile stage in a mammalian vertebrate host [9], where the parasites infect cells of the phagocytic mononuclear system, where the macrophages are the main cellular compartment in the vertebrate host [10].…”
Section: Introductionmentioning
confidence: 99%
“…Leishmania parasites are transmitted to humans through the bite of female sandflies of the genera Lutzomyia and Phlebotomus. Like many protozoan parasites, Leishmania parasites have a digenetic lifecycle: an extracellular mobile stage (promastigote), exclusive to the invertebrate host, and an intracellular (amastigote) non-mobile stage in a mammalian vertebrate host [9], where the parasites infect cells of the phagocytic mononuclear system, where the macrophages are the main cellular compartment in the vertebrate host [10].…”
Section: Introductionmentioning
confidence: 99%
“…Leishmaniasis is an example of a tropical disease, which is caused by protozoan parasites belonging to the genus Leishmania, predominantly affecting African, Asian and Latin American countries. [88] Chemotherapy is its standard treatment, but it is strongly associated with high toxicity and low efficiency with limited patients compliance of such endemic regions and new treatments are thus being proposed. [89] A potent imidazo [1,2-a]pyrazine-based antileishmanial compound has been reported by Bazin et al to target L-CK1.2 at low micromolar ranges.…”
Section: Applications Of Volatile Nitrogenous Compounds In Neglected Tropical Diseasesmentioning
confidence: 99%
“…Oliveira et al summarized the challenges in tackling multi-resistant leishmania. 10 With the development of nanocapsules for antimicrobials, the bioavailability of drugs has been improved and effective to combat parasitic resistance, with lower side effects and enhanced treatment efficacy. Nanoparticles encapsulated with essential oils and bupivacaine have also been shown to be an effective treatment of melanoma, which can lead to the development of skin cancer, as reported by Geronimo et al 11 This formulation also showed high physical and chemical stability within one year.…”
Section: In Focus: Latest Development Of Nanotechnology In Latin Americamentioning
confidence: 99%